Design and development fo a CCD based optical tomography measuring system for particle sizing identification - Mariani, Idroas; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; M. N., Ibrahim; Green, R. G. (Elsevier Ltd, 2011)
Link to publisher's homepage at http://www.elsevier.com/